Analysis of Parking Needs at Sakura Mart Amurang - Sumajouw, Josep; Kabo, Don; Nicolaas, Seska (Formosa Journal of Sustainable Research, 2024)
Sakura Mart is the largest shopping center in Amurang City, North Sulawesi, Indonesia. At Sakura Mart Amurang the parking facilities cannot accommodate parking needs. This analytical research aims to calculate the parking space requirements that must be provided for visitors when in the Sakura Mart Amurang parking area. The steps taken include calculating parking volume, parking accumulation, parking duration, parking capacity, parking availability, parking index, parking turnover rate, analysis of parking space requirements, and vehicle waiting time. The total shortage of parking space for two-wheeled vehicles is 92 spaces, while for four-wheeled vehicles 23 spaces must be provided with a total area of 516 m². For the time being, to reduce existing parking capacity, a maximum vehicle waiting time of 11 minutes 30.6 seconds for two-wheeled vehicles and 19 minutes 0.015 seconds for four-wheeled vehicles is used. Waiting time limits in parking areas must be emphasized so that they can accommodate all vehicles that come to park their vehicles, then by providing rates and multiples of rates after the specified waiting time has passed, it can encourage vehicle owners not to linger in the parking lot. area. parking area. parking area. The arrangement of the parking area must be considered with a good and correct parking management system for the convenience of parking users at Sakura Mart Amurang